Reductions in Hospital Admissions and Delays in Acute Stroke Care During the Pandemic of COVID-19 - Wu, Yiqun; Chen, Fei; Wang, Zijing; Feng, Wuwei; Liu, Ying; Wang, Yuping; Song, Haiqing (Frontiers in Neurology, 2020)
Background: Rapid and effective medical care for stroke is paramount to achieve maximal functional recovery. Because of the wide spreading of the coronavirus disease in 2019 (COVID-19), acute stroke care is negatively impacted. How much acute care for stroke has been affected during the pandemic remains to be assessed. Methods: The first-level response to major public health was launched from January 24th to April 29th, 2020 in Beijing to contain the spread of COVID-19. Based on a database connecting all 77 stroke centers, the quantity and quality in emergency care for stroke during the 97 lockdown days were compared with the equivalent period in 2019. During the pandemic, 15 of the 77 stroke centers were designated to receive patients sick with COVID-19. Subgroup analyses were carried out by different types of hospitals (designated and undesignated). Results: There were 1,281 and 2,354 stroke emergency hospital admissions in the lockdown period and the parallel period in 2019, respectively. A reduction of 45.6% in admission was shown in the lockdown period, with more reductions for hemorrhagic stroke (69.0%) compared with ischemic stroke (42.9%). More reductions happened in COVID-19 designated hospitals (52.6%) compared with undesignated hospitals (41.8%). The mean NIHSS score at hospital arrival was significantly higher in the lockdown period (9.4 ± 7.7 in 2020 vs. 8.4 ± 7.8 in 2019, P < 0.001). For the metrics measuring the quality of acute stroke care, the onset to door (OTD), onset to needle (ONT), and onset to recanalization (OTR) times didn't change significantly, while significant delays are shown for the door to CT scan (DTC, 1 min delay), door to needle (DTN, 4 min delays), and door to puncture (DTP, 29 min delays) times, which mainly happened in COVID-19 undesignated hospitals. Conclusions: Profound reductions in stroke hospital admissions and significant delays in emergency care for acute ischemic stroke occurred during the pandemic of COVID-19. Engagement and effective communication with all stakeholders including patients, health care providers, governmental policymakers, and other implementation partners are required for future success in similar crises.